5G new radio : a beam-based air interface - Enescu, Mihai, 1974- (Hoboken, NJ, USA : Wiley, 2020)
"This book presents the newly 3GPP-specified 5G physical layer, focusing on the beam-based operation which is a new dimension in the radio system due to the millimeter wave deployments of 5G. The intention is to complement the 3GPP specification and connect the dots of key features. The expert authors, all contributors to creating the actual standard, will cover the physical layer aspects related to beam operation, such as initial access, details of reference signal design, beam management, DL and UL data channel transmission. The book will contain a brief overview of standardization efforts, IMT-2020 submission, 5G spectrum and will also contain performance analysis of 5G components. The book assumes a basic knowledge of multi-antenna technologies"--
BIBINDX
Keywords: 5G mobile communication systems; Radio; Electronic books